Tetraria triangularis (Boeck.) C.B. Clarke and the Cape fold archipelago : an analysis of genetic and morphological variation in a high-altitude species native to the moutains of the Cape floristic region - Britton, Matthew Newton (Department of Biological Sciences, 2015)
Includes bibliographical references (leaves 102-127).